Monitoring of prestress and bond stress of self-sensing FBG steel strand. (June 2021) - Zhu, Wanxu; Shen, Quanxi; Qin, Heying
Highlights: A quasi-distributed fiber Bragg grating (FBG) sensor is encapsulated in a longitudinal groove. The strain transfer rate between FBG sensor and matrix material reaches 99%. The stress distribution along the longitudinal direction of the unbonded prestressed FBG steel strand is not equal. The maximum monitoring error of FBG sensor is only 3.42%. The FBG sensor can monitor the stress distribution of the steel strand and the development trend of the bond stress. Abstract: In order to investigate the stress distribution in a prestressed steel strand and the development of bond stress between the steel strand and concrete, a new technology of encapsulating quasi-distributed fiber Bragg grating (FBG) sensor in a longitudinal groove of the center wire of a steel strand is proposed. Based on the theoretical analysis of the strain transfer between the FBG sensor and the substrate, specific parameters for measuring the stability of the FBG sensor are discussed. Tension and bending tests on unbonded prestressed reactive powder concrete beams are carried out to explore the self-sensing steel strand characteristics. The test results indicate that the quasi-distributed FBG sensor encapsulated in the center wire of the steel strand can monitor the stress distribution in the steel strand and the damage of the beam efficiently, and the maximum tensile monitoring error is only 3.42%. To analyze the distribution of the prestress and bond stress of steel strand along the anchorage length, the tensile tests are carried out on the self-sensing steel strand. The results show that the quasi-distributed FBG sensor can accurately measure the variations in steel strand stress and bond stress along the anchorage length during the tensile process.